1988
DOI: 10.1002/aic.690341112
|View full text |Cite
|
Sign up to set email alerts
|

Study of the adsorption and desorption of multiple adsorbates in a fixed bed

Abstract: An experimental and theoretical study was made of the adsorption of ethanelpropane mixtures from nitrogen or helium. The study also covered the desorption of the mixtures using a purge of hot nitrogen or helium. The adsorbent was Witco JXC activated carbon. A nonequilibrium, mechanistic model was developed and was shown to represent both adsorption and desorption processes. The model utilized mixture isotherm data predicted by the Flory Huggins form of the vacancy solution model. Both adsorption and hot purge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 36 publications
3
51
0
Order By: Relevance
“…The well-known roll-up phenomenon results from the Adsorption bed wd\ initidlly LatUrdted with H 2 at 299 15 K and 10 dtm fact that weakly adsorbed components lose their adsorption sites due t o the competitive adsorption of more strongly adsorbed components that follow the preceding wavefronts of weakly adsorbed components. The desorbed adsorbates join the bulk stream and increase the concentration more than feed concentration (Huang and Fair, 1988;Chlendi et al, 1995).…”
Section: Breakthrough Curvesmentioning
confidence: 99%
See 1 more Smart Citation
“…The well-known roll-up phenomenon results from the Adsorption bed wd\ initidlly LatUrdted with H 2 at 299 15 K and 10 dtm fact that weakly adsorbed components lose their adsorption sites due t o the competitive adsorption of more strongly adsorbed components that follow the preceding wavefronts of weakly adsorbed components. The desorbed adsorbates join the bulk stream and increase the concentration more than feed concentration (Huang and Fair, 1988;Chlendi et al, 1995).…”
Section: Breakthrough Curvesmentioning
confidence: 99%
“…The stoichiometric breakthrough times are comparable to the experimental and predicted breakthrough times. Because of the preferential and competitive adsorption among the adsorbates, the kinetic effects of the adsorption rate, and temperature variations in the adsorption bed, the stoichiometric breakthrough times of a PSA process may shift to the left or right of the experimental breakthrough times (Huang and Fair, 1988).…”
Section: Breakthrough Curvesmentioning
confidence: 99%
“…The well-known roll-up phenomenon results from the fact that weakly adsorbed components lose their adsorption sites due to the competitive adsorption of the stronger adsorbed components that follow the preceding wavefronts of weakly adsorbed components. The desorbed adsorbates join the bulk stream and increase the concentration more than the feed concentration [8,23]. These breakthrough curve phenomena were reflected in the temperature profile.…”
Section: Single Adsorbent Bedmentioning
confidence: 99%
“…Regeneration is expected to be complete when effluent gas temperature reaches to regeneration temperature 26 , however this is not applicable to adiabatic systems. Regeneration time is also defined as time at which effluent gas concentration reaches 1% of feed gas concentration 25,27 . Urano et al 28 reported following five elementary processes taking place during steam regeneration of spent granulated activated carbon (GAC) from waste water treatment plant.…”
Section: Steam Regenerationmentioning
confidence: 99%